Fermat numbers and Fibonacci numbers on Heron triangles - Chinnawat Tangkanchanawong; Sawian Jaidee (Songklanakarin Journal of Science and Technology (SJST), 2022)
We mainly give necessary and sufficient conditions for being a Heron triangle in the case of certain classes of an isosceles triangles with the three sides (𝑎, 𝑎, 𝑐), where 𝑐 is an arbitrary positive integer, and 𝑎 is a Fermat or Fibonacci prime.